Aproximación del ‘utilitarismo de reglas’ basado en el personalismo como alternativa a la discusión bioética del perfeccionamiento genético de la especie humana - Villanueva Sardón, Rodrigo José (2022)
Contemporary bioethical discussion confronts us with complex dilemmas such as the application of genetic improvement of humanity. These types of ethical conflicts call into question the value we place on the human person in contrast to the search for the greatest social welfare. Positions such as personalism, which responds to an ontological philosophical approach, and utilitarianism, from its normative approach, allow us to address this confrontation. However, these proposals are often presented as opposing or incompatible, as we can see in the discussion of the arguments, bioconservative of Sandel and transhumanist of Savulescu, on the dilemma of genetic improvement. Therefore, the present research work intends to demonstrate that it is possible to put in dialogue and seek to integrate personalism and rule utilitarianism. This approach called "personalist utilitarianism" seeks the implementation of an ideal moral rule, which in this case would be the personalist rule, whose use would ensure the maximization of social welfare without detriment to the value of the person.